Preparation of TiO2 nanoparticles by sparking technique for enhancing photovoltaic performance of dye-sensitized solar cells - Orawan Wiranwetchayan (2018)
© 2017, Springer Science+Business Media Dordrecht. The double-layer photoanodes fabricated from TiO2 nanoparticles (np-TiO2) and TiO2 powder (P25) for dye-sensitized solar cells (DSSCs) are reported. The np-TiO2 was deposited on FTO substrates by a sparking technique. The PT1 and PT2 DSSCs were composed of FTO/P25/np-TiO2/N719/electrolyte/Pt and FTO/np-TiO2/P25/N719/electrolyte/Pt, respectively. The Nyquist plot and equivalent circuit of impedance of the DSSCs are also explained and discussed. In this research, the PT1 DSSC with a 1 h sparking period has the highest efficiency of 3.62, 50.21% higher than that of the reference. The enhancement is explained by the increase of adsorption of dye molecules that lead to a remarkable improvement in short-circuit photocurrent (Jsc). The pore size distribution with increasing the film thickness played a role in the penetration of the electrolyte, dye molecules and effective surface area. Moreover, a decrease in the interfacial resistance was detected in the P25/np-TiO2 double-layered photoanode, leading to fast charge transport and decreased charge recombination in DSSCs.